Digitalization in small business for women entrepreneurs in Ukraine - Kolarov, Kostadin Goranov; Kononenko, Igor Volodymyrovich; Grinchenko, Marina Anatoliyvna; Bukrieieva, Karina Sergiyivna (Національний технічний університет "Харківський політехнічний інститут", 2021)
From September 2020 to April 2022, the “DIGI-WOMEN, digital entrepreneurship tools and support for women entrepreneurs” project is being implemented within the “Erasmus +” program. Project coordinator - is the University of National and World Economy, Sofia, Bulgaria. Project partners are National Technical University “Kharkiv Polytechnic Institute”, Ukraine; Bit-management Beratung Gesmbh, Austria; Baltijas Juras Regiona Klasteru Eksperti, Latvia; Consulenza Direzionale di Paolo Zaramella, Italy; CEPOR Centar za politiku razvoja malih i srednjih poduzeća i poduzetništva, Croatia; Greek Association of Women Entrepreneurs – SEGE, Greece. Project overall objective is to develop a training program that will train experts in order to offer trainings and mentorship sessions that are tailored to the needs of the female entrepreneurs digitalizing their business and help them overcome the obstacles they face in the digitalization. As a result of analyzing the relevance of digitalization in small business for women entrepreneurs in Ukraine the conclusion was made that important areas of digitalization are: search for ideas for business and substantiate these ideas using digital technologies; creation and promotion of business websites; presentation and promotion of business in social networks; implementation of a CRM system at the enterprise. A training program is proposed to prepare experts who will then train women entrepreneurs who run small businesses. The program is designed in such a way that women entrepreneurs have mastered precisely those areas of knowledge that are recognized as the most important in the studies. The program consists of a number of trainings on the following topics: "Training techniques for women entrepreneurs in small business", "Search and Substantiation of Ideas for Business", "Development, deployment, analysis and promotion of the web site ", "Introduction to Social Media Marketing (SMM), "Implementation of digital technologies on the example of the Bitrix24 CRM system".

З вересня 2020 по квітень 2022 року в рамках програми "Erasmus +" здійснюється проект "DIGI-WOMEN, digital entrepreneurship tools andsupport for women entrepreneurs". Координатор проекту - University of National and World Economy, Софія, Болгарія. У проекті беруть участь Національний технічний університет «Харківський політехнічний інститут», Україна; Bit-management Beratung Gesmbh, Австрія; Baltijas Juras Regiona Klasteru Eksperti, Латвія; Consulenza Direzionale di Paolo Zaramella, Італія; CEPOR Centar za politiku razvoja malih i srednjih poduzeća i poduzetništva, Хорватія; Greek Association of Women Entrepreneurs - SEGE, Греція. Головна мета проекту - розробити навчальну програму для підготовки фахівців, які потім будуть проводити тренінги та повчальні заняття для жінок-підприємців малого бізнесу. Програма повинна враховувати потреби підприємниць, які цифровізуют свій бізнес, і допомагати їм долати перешкоди, з якими вони стикаються на цьому шляху. В результаті аналізу актуальності цифровізації малого бізнесу жінок-підприємців в Україні прийшли до висновку, що важливими напрямками цифровізації є: пошук ідей для бізнесу та обґрунтування цих ідей за допомогою цифрових технологій; створення і просування сайтів компаній; представлення та просування бізнесу в соціальних мережах; впровадження на підприємствах CRM-систем. Пропонується програма тренінгів для підготовки експертів, які потім будуть навчати жінок-підприємців малого бізнесу. Програма складена таким чином, щоб жінки-підприємці освоїли саме ті галузі знань, які в проведених дослідженнях визнані найбільш важливими. Програма складається з ряду тренінгів на наступні теми: «Методики викладання для жінок-підприємців малого бізнесу», «Пошук і обгрунтування ідей для бізнесу», «Розробка, розміщення, аналітика і просування власного веб-сайту», «Введення в Social Media Marketing (SMM), «Впровадження digital-технологій на прикладі CRM системи Бітрікс24».
Цифровізація малого бізнесу жінок-підприємців в Україні
Keywords: Erasmus+; project; curriculum; Erasmus +; проєкт; навчальна програма